The Suspicion of Virtue : Women Philosophers in Neoclassical France - Conley, John J. (Cornell University Press, 2018)
The salon was of particular importance in mid- to late-seventeenth-century France, enabling aristocratic women to develop a philosophical culture that simultaneously reflected and opposed the dominant male philosophy. In The Suspicion of Virtue, John J. Conley, S.J., explores the moral philosophies developed by five women authors of that milieu: Madame de Sablé, Madame Deshoulières, Madame de la Sabliére, Mlle de la Vallière, and Madame de Maintenon. Through biography, extensive translation, commentary, and critical analysis, The Suspicion of Virtue presents the work of women who participated in the philosophical debates of the early modern period but who have been largely erased from the standard history of philosophy. Conley examines the various literary genres (maxim, ode, dialogue) in which these authors presented their moral theory. He also unveils the philosophical complexity of the arguments presented by these women and of the salon culture that nurtured their preoccupations. Their pointed critiques of virtue as a mask of vice, Conley asserts, are relevant to current controversy over the revival of virtue theory by contemporary ethicians.